PENGARUH TINGKAT SUKU BUNGA DAN JANGKA WAKTU TERHADAP KREDIT MACET (STUDI KASUS PADA KOPERASI SYARIAH MASYARAKAT KERTASINDUYASA, JATIBARANG, BREBES) - Solikha Puji Astuti; Dwi Harini; Slamet Bambang Riono (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2022)
The purpose of this study is to determine the effect of interest rates and timeframes on bad debts. This research was conducted at the Sharia Cooperative of the Kertasinduyasa Society, Brebes with a population of 50 respondents. The data collection method in this study was carried out by distributing questionnaires to respondents who had bad debts in the cooperative. The data analysis used is an instrument test which includes validity test and reliability test, classical assumption test which includes normality test, multicollinearity test, and heteroskedasticity test, hypothesis test which includes t test and f test and determination test. From the results of the test conducted, it was concluded that there was a significant influence of the interest rate variable on the bad loan variable with a significance value of 0.007 < 0.05, while the time period variable had no significant effect on the bad credit variable with a significance value of 0.872 > 0.05.